SOCIAL STUDIES LEARNING MODELS THAT FOSTER SOCIAL LITERACY AND CIVIC ENGAGEMENT AMONG HIGH SCHOOL STUDENTS - Rasyid Lafahrozi Pramudita (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to develop an integrated IPS learning model that strengthens social literacy and civic engagement among senior high school students in Indonesia, addressing the persistent gap between social understanding and active participation. Using a library research design, this study systematically analyzed peer-reviewed articles, policy documents, and empirical studies published within the last five years to identify pedagogical strategies proven effective in promoting social-civic competencies. The findings reveal that learning models incorporating inquiry-based approaches, dialogic interaction, digital citizenship tools, and experiential civic tasks significantly enhance students’ ability to interpret social issues, construct arguments, and participate in community-oriented activities. The results also indicate that traditional content-focused social studies (IPS) instruction remains insufficient for building the higher-order thinking and participatory skills needed in contemporary citizenship education. The novelty of this study lies in its formulation of a unified, context-responsive IPS model that synthesizes social literacy development with civic engagement outcomes, bridging theoretical and practical components often treated separately in previous research. Furthermore, the proposed model integrates technological and experiential elements to align with the civic demands of the digital era. Overall, this research contributes to global discussions on transformative civic education by offering a scalable and adaptable framework that can prepare students to become informed, critical, and responsible citizens. The study concludes that the integrated IPS model provides a promising direction for enhancing civic learning in diverse educational contexts and underscores the need for participatory, reflective, and digitally enriched social studies pedagogy.